2017
DOI: 10.1038/mi.2016.125
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase 2 promotes enterocyte survival and goblet cell differentiation in the inflamed intestine

Abstract: c-Jun N-terminal kinases (JNKs) contribute to immune signaling but their functional role during intestinal mucosal inflammation has remained ill defined. Using genetic mouse models, we characterized the role of JNK1 and JNK2 during homeostasis and acute colitis. Epithelial apoptosis, regeneration, differentiation, and barrier function were analyzed in intestinal epithelium-specific (ΔIEC) or complete JNK1 and bone marrow chimeric or complete JNK2 deficient mice as well as double-knockout animals (JNK1JNK2) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Previous studies showed that treatment with JNK inhibitors (e.g. SP600125) attenuated DSS-induced colitis in rodent models [ [28] , [29] , [30] ] and play critical roles in regulating colon homeostasis [ 31 ], however, genetic ablation of JNK1 or JNK2 increased DSS-induced colitis in mice [ [32] , [33] , [34] ]. Regarding its roles in CRC, JNK overexpression exacerbated AOM/DSS-induced CRC, but had little impact on tumorigenesis triggered by Apc mutation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that treatment with JNK inhibitors (e.g. SP600125) attenuated DSS-induced colitis in rodent models [ [28] , [29] , [30] ] and play critical roles in regulating colon homeostasis [ 31 ], however, genetic ablation of JNK1 or JNK2 increased DSS-induced colitis in mice [ [32] , [33] , [34] ]. Regarding its roles in CRC, JNK overexpression exacerbated AOM/DSS-induced CRC, but had little impact on tumorigenesis triggered by Apc mutation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In intestinal homeostasis, inflammation, and cancer, the critical function of c-Jun has been studied extensively. [8][9][10][11][12][13] ATF2 is one of the potential heterodimer partners of c-Jun and is known to be regulated by pathways that play a critical role in the intestinal epithelium such as the Wnt and bone morphogenetic protein pathways. [14][15][16][17][18] Moreover, ATF2 contains an N-terminal activation domain that, as for c-Jun, can be activated by several mitogen-activated protein kinases (MAPKs), which have been implicated to play an important role in immune maintenance, hence regulating immune responses.…”
mentioning
confidence: 99%
“…JNK1 and JNK2 are widely expressed, while JNK3′s expression is predominantly restricted to the brain, heart and testis. Studies suggest that the activation of JNK1 may induce apoptosis, whereas JNK2 inhibits it . At least four alternatively spliced transcript variants of JNK1 exist, including two short JNK1 isoforms (JNK1‐a1 and JNK1‐b1) and two long JNK1 isoforms (JNK1‐a2 and JNK1‐b2).…”
Section: Resultsmentioning
confidence: 99%
“…19]. At least four alternatively spliced transcript variants of JNK1 exist, including two short JNK1 isoforms (JNK1-a1 and JNK1-b1) and two long JNK1 isoforms (JNK1-a2 and JNK1-b2).…”
mentioning
confidence: 99%